Protein kinase C epsilon activation regulates proliferation, migration, and epithelial to mesenchymal-like transition in rat Schwann cells - Mohamed, Tasnim; Colciago, Alessandra; Montagnani Marelli, Marina; Moretti, Roberta Manuela; Magnaghi, Valerio (Frontiers in Cellular Neuroscience, 2023)
Protein kinase type C-ε (PKCε) plays important roles in the sensitization of primary afferent nociceptors, promoting mechanical hyperalgesia. Recently, PKCε was implicated also in the control of cell proliferation, in promoting mitogenesis and metastasis in several cancers.Previously, we showed that PKCε is present in sensory neurons of the peripheral nervous system, participating in the control of pain onset and chronification. However, its role in Schwann cells (SCs) is still not investigated. Herein, by means of the PKCε agonist DPC-LA 500nM, we report that PKCε is involved in SCs switch from the proliferative toward the differentiated state; indeed, proliferation (cell count) was decreased while migration (scratch test and Boyden assay) and markers of SC differentiation (qRT-PCR and WB) were increased.The brain derived neurotrophic factor (BDNF), though TrkB activation, at least autocrinally controls SCs proliferation via PKCε. Importantly, PKCε activation likely promoted a partial epithelial-mesenchymal transition (EMT) of rat SCs. Overall, PKCε posits a novel function in the transformation of SCs, assuming a role in the mechanisms controlling SCs fate and plasticity.